Effect of premeal consumption of whey protein and its hydrolysate on food intake and postmeal glycemia and insulin responses in young adults - Akhavan, Tina; Luhovyy, Bohdan L; Brown, Peter H; Cho, Clara E; Anderson, G. Harvey (The American journal of clinical nutrition, 2010)
BACKGROUND: Dairy protein ingestion before a meal reduces food intake and, when consumed with carbohydrate, reduces blood glucose. OBJECTIVE: The objective was to describe the effect of whey protein (WP) or its hydrolysate (WPH) when consumed before a meal on food intake, pre- and postmeal satiety, and concentrations of blood glucose and insulin in healthy young adults. DESIGN: Two randomized crossover studies were conducted. WP (10-40 g) in 300 mL water was provided in experiment 1, and WP (5-40 g) and WPH (10 g) in 300 mL water were provided in experiment 2. At 30 min after consumption, the subjects were fed an ad libitum pizza meal (experiment 1) or a preset pizza meal (12 kcal/kg, experiment 2). Satiety, blood glucose, and insulin were measured at baseline and at intervals both before and after the meals. RESULTS: In experiment 1, 20-40 g WP suppressed food intake (P < 0.0001) and 10-40 g WP reduced postmeal blood glucose concentrations and the area under the curve (AUC) (P < 0.05). In experiment 2, 10-40 g WP, but not WPH, reduced postmeal blood glucose AUC and insulin AUC in a dose-dependent manner (P < 0.05). The ratio of cumulative blood glucose to insulin AUCs (0-170 min) was reduced by ≥10 g WP but not by 10 g WPH. CONCLUSIONS: WP consumed before a meal reduces food intake, postmeal blood glucose and insulin, and the ratio of cumulative blood glucose to insulin AUCs in a dose-dependent manner. Intact WP, but not WPH, contributes to blood glucose control by both insulin-dependent and insulin-independent mechanisms. This trial was registered at clinicaltrials.gov as NCT00988377 and NCT00988182.